Gastrointestinal Bleeding on Call: Questions and Answers and One Person's Opinions - Funaki, Brian (Seminars in Interventional Radiology, 2020)
Gastrointestinal (GI) bleeding represents one of the more morbid forms of hemorrhage that interventional radiologists deal with on an on-call basis. Bleeding from the GI tract takes many forms and has many etiologies. While venous bleeds from varices are often treated emergently with placement of a transjugular intrahepatic portosystemic shunt, arterial hemorrhages are treated most effectively with embolization procedures. Embolization must be performed in specific ways, however, in an effort to decrease the risk of bowel ischemia; this also requires choosing the right patients in whom to perform embolization procedures. This article will provide a discussion on when to perform embolization and how, what to do with specific patient populations such as those with coagulopathy, and which patients should be considered for emergent treatment versus those that can be postponed.
Keywords: interventional radiology; hemorrhage; gastrointestinal bleeding; embolization